HsDHODH Microdomain-Membrane Interactions Influenced by the Lipid Composition - Vicente, Eduardo F. [UNESP]; Sahu, Indra D.; Crusca, Edson [UNESP]; Basso, Luis G. M.; Munte, Claudia E.; Costa-Filho, Antonio J.; Lorigan, Gary A.; Cilli, Eduardo M. [UNESP] (American Chemical Society (ACS), 2017)
Human dihydroorotate dehydrogenase (HsDHODH) enzyme has been studied as selective target for inhibitors to block the enzyme activity, intending to prevent proliferative diseases. The N-terminal microdomain seems to play an important role in the enzyme function. However, the molecular mechanism of action and dynamics of this region are not totally understood yet. This study analyzes the interaction and conformation in model membranes of HsDHODH microdomain using peptide analogues containing the paramagnetic amino acid TOAC at strategic positions. In buffer solution, the analogues presented a disordered conformation, but acquired a high content of α-helical structure in membrane mimetics, which was found to be lipid dependent. The microdomain peptide structure in micelles showed a very different peptide conformation when compared to the reported crystal structure, displaying a conformational flexibility of its helices, promoted by the connecting loop, which might be functionally relevant. Electron spin resonance in membrane compositions containing POPC, POPE, and cardiolipin showed that interaction of the analogues was enhanced by the presence of cardiolipin, indicating that the microdomain preferentially interacts with cardiolipin-containing membranes. Therefore, the great flexibility of the microdomain and the cardiolipin affinity should be considered in further studies aimed at finding new inhibitory compounds to fight proliferative diseases.